(untitled) (Fiep Bulletin - online, 2014)
This article deals with the conception of today’s body, its construction and dynamics, as well as its dimension as an agent of social and cultural relationships. The issue is thought from the insertion of the body as signifier and signified in the context of physical education. What we intend is to show that there is an open space to discuss the phylosophical, historical and cultural idea of the body, especially today, when there are many “alternative” ways to work the body - like the Yoga - and many other body techniques which see the body as a whole. The ideas concerning the body’s health and beauty are values inspired in the Greek ideals. We trace the line of the physical education in Brazil in the twentieth century so as to define the limits of the body in view of the ideal body as well as reality. Proceeding, we question the worthiness of the body in view of Nietzsche’s values. Finally, we point out the possibility of a discussion of what I call the cult of the body and the art of existence. Our reflections point to the Cult of the Body, which seems to show the crisis of today’s body. Differently from the classical thought, the construction of today’s body is permeated by the need to have a kind of body to stop being. Here, the reference is the myth of the post-modernity, which in the Nietzcshean sense, makes the permanent reconstruction of the body in its conceptual form possible. Under this light, we understand that the liveliness of the re-construction of the body is in the Are of the Existence, an expression borrowed from Michel Foucault who, in his work entitled The History of Sexuality, says: “It was [the] theme of the care of oneself, consecrated by Socrates, that later philosophy took up again and ultimately placed at the center of that "art of existence”.